2015
DOI: 10.12678/1089-313x.19.2.70
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Evaluation of the Classical Ballet Step “Plié”

Abstract: Lack of alignment between the lowerlimb structures, such as the hips, knees, and longitudinal arches of the feet, has been described as an important predisposing factor in musculoskeletal injury among classical ballet dancers. However, no studies were found that analyzed basic ballet movements with quantification of objective criteria of the movements. The purposes of this study were: 1. to establish a methodology to quantify, using kinematic evaluation, the technical criteria that guide the correct execution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 32 publications
0
28
0
1
Order By: Relevance
“…Although, this strong static musculoskeletal control may not necessarily extend to quick dynamic dance movements. According to Gontijo et al [43] arch height stability classification, some of the dancers who demonstrated ‘excellent stability’ in both static first positions experienced dynamic ‘instability’ during sautés landings. These dancers demonstrating increased dynamic arch ‘instability’, and therefore, potentially are exposing the posterior tibial muscle to excessive eccentric forces and tensile loads [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, this strong static musculoskeletal control may not necessarily extend to quick dynamic dance movements. According to Gontijo et al [43] arch height stability classification, some of the dancers who demonstrated ‘excellent stability’ in both static first positions experienced dynamic ‘instability’ during sautés landings. These dancers demonstrating increased dynamic arch ‘instability’, and therefore, potentially are exposing the posterior tibial muscle to excessive eccentric forces and tensile loads [47].…”
Section: Discussionmentioning
confidence: 99%
“…Navicular height in relation to the laboratory coordinate system (in millimetres) was analysed with the variation in height from the natural double leg up-right posture indicating navicular drop. Navicular drop was classified into three types of arch height stability according to Gontijo et al [43]: 1. ‘excellent stabilisation’ navicular drop < 7 mm); 2.…”
Section: Methodsmentioning
confidence: 99%
“…Increasing hip joint ROM is especially challenging and may result in loading the sacroiliac joint and lumbar spine (DeMann, 1997; Bronner and Ojofeitimi, 2011) if not done correctly (DeMann, 1997; Deckert et al, 2007; Gontijo et al, 2015). The developpé is a core ballet movement consisting of lifting the leg, performed routinely by dance students of all ages and levels of expertise.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic pelvic alignment (Franklin, 2012, 2014; Gontijo et al, 2015) and pelvic control (Gildea et al, 2015) are other important components for developpé performance (Holt et al, 2011), serving as a key element for whole-body axial postural alignment (Keller and West, 1995; DeMann, 1997; Wilson et al, 2004; Gontijo et al, 2015) and for facilitating efficient movement at the hip joint (Deckert et al, 2007). Correct pelvic dynamic alignment synchronized with the hip motion (known as “pelvi-femoral rhythm” (Bohannon et al, 1985; Murray et al, 2002) contributes to full hip ROM and efficient lower extremity motion (DeMann, 1997), especially in extreme positions such as developpé (Norkin and Levangie, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation